2022
DOI: 10.3802/jgo.2022.33.e83
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal dissemination of high-grade serous ovarian cancer: pivotal roles of chromosomal instability and epigenetic dynamics

Abstract: Epithelial ovarian cancer remains the lethal gynecological malignancy in women. The representative histotype is high-grade serous carcinoma (HGSC), and most patients with HGSC present at advanced stages with peritoneal dissemination. Since the peritoneal dissemination is the most important factor for poor prognosis of the patients, complete exploration for its molecular mechanisms is mandatory. In this narrative review, being based on the clinical, pathologic, and genomic findings of HGSC, chromosomal instabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…Therefore, we aimed to classify the JGOG-TR2 tumors based on molecular features rather than morphological findings. Since chromosomal instability is one of the most characteristic molecular features of HGSC (#58), we focused on CNV signature-based analysis (#59).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we aimed to classify the JGOG-TR2 tumors based on molecular features rather than morphological findings. Since chromosomal instability is one of the most characteristic molecular features of HGSC (#58), we focused on CNV signature-based analysis (#59).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, these studies demonstrated that early tumors of serous intratubal carcinoma in the fallopian tube already have important DNA changes necessary for OC development. These findings suggest that serous fallopian tube carcinoma migrated to the ovary and carcinoma progressed in the ovary [ 47 , 48 , 50 ] ( Fig. 1 ).…”
Section: Fallopian Tube Epithelium As the Origin Of Serous Ovarian Ca...mentioning
confidence: 99%
“…Some researchers have attributed the most common type of OC to the fallopian tube, a thin fibrous tube connecting the ovary to the uterus. Previous findings obtained from nine OC patients indicated that the genomic origin of many ovarian tumors was the fallopian tube [ 47 , 48 ]. Previous studies provided insights into the origin of OC and the potential of novel interventions for the prevention and treatment of OC.…”
Section: Fallopian Tube Epithelium As the Origin Of Serous Ovarian Ca...mentioning
confidence: 99%
See 1 more Smart Citation
“…STIC could be a likely precursor lesion of high-grade serous pelvic carcinomas, carcinosarcoma, and undifferentiated carcinoma with an incidence of 0.6–7% in breast cancer 1/2 gene carriers or women with a strong family history of breast or ovarian carcinoma. Therefore, epithelial malignant cells and STICs that occur in the epithelial cell tissue of the fallopian tubes and in the fimbriated end are the primary tumors that metastasize into the ovary and form micrometastases [ 16 , 17 , 18 ]. In forming a micrometastatic niche in multiple organs, epithelial and stromal cells in contact with circulation tumor cells (CTCs) are initialized by secretory factors from CTCs that compose the micrometastatic niche [ 8 , 9 , 10 , 11 ].…”
Section: Case Reportmentioning
confidence: 99%